Effect Of A Token Economy Training Program In Reducing Inattention And Hyperactivity Among Female Students With Learning Disabilities In Saudi Arabia - Al Jawabra, Wafa Fawwaz M (2017)
This study aimed at evaluating the effect of the token economy training program in reducing inattention and hyperactivity among female students with learning disabilities in resource rooms. In this study, a quasi-experimental method was used. The sample of the study consisted of female students who had been identified from those who gained the highest grades on the marginal scales of the behavioral problems related to inattention and hyperactivity. They were randomly classified into two groups: The first was an experimental group that received the token economy program and consisted of 30 students, experimental group 1 (15 students) and experimental group 2 (15 students).